(untitled) (Quinto Sol, 2019)
Based on the verification of non-alphabetical forms of register and archive in indigenous societies, as well as a definition of the archive as that which provides these heterogeneous registers with readability and effectiveness, the following question arises: how to understand the power of a certain type of objects that seem to base their power on the fact of escaping from codes and representations? We propose a conceptualization of the indigenous archives opposed to the modern figure of the archive as an empty space and destined to the collection and organization of "fetishes" subjected to a representational function. On the contrary, these indigenous archives would function as fetishes in themselves, that is, as montages of registers and objects in which the image of their power and effectiveness is materialized. Finally we see how this type of file corresponds to political forms not based on the modern principle of state sovereignty, but rather oriented towards the production and registration of alliances. In this framework, the notion of mimesis and simulacrum will be used as a condition of this non-state form of organizing power and its archives.